Impact of Seminal Plasma Antioxidants on Donkey Sperm Cryotolerance - Jaime Catalán; Iván Yánez-Ortiz; Asta Tvarijonaviciute; Luis Guillermo González-Arostegui; Camila P. Rubio; Marc Yeste; Jordi Miró; Isabel Barranco (MDPI AG, 2022)
This study investigated whether the activities of the antioxidant components of donkey seminal plasma (SP)-both enzymatic (superoxide dismutase (SOD), catalase-like (CAT), glutathione peroxidase-like (GPX), and paraoxonase type 1 (PON1)) and non-enzymatic (measured in terms of total thiol, copper-reducing antioxidant capacity (CUPRAC), ferric-reducing ability of plasma (FRAP), and Trolox equivalent antioxidant capacity (TEAC))-and oxidative stress index (OSI) are related to sperm cryotolerance. For this purpose, 15 ejaculates from jackasses (one per individual) were collected and split into two aliquots. The first one was used for measuring the activities levels of enzymatic and non-enzymatic antioxidants and OSI in SP, whereas the other aliquot was cryopreserved. Before cryopreservation, sperm quality parameters (concentration, motility, and viability) were evaluated. After thawing, sperm motility, plasma membrane integrity, lipid disorder, mitochondrial membrane potential, reactive oxygen species (ROS), and calcium intracellular levels were also determined. Based on the percentages of total motility (TM) and of sperm with an intact plasma membrane (SYBR14+/PI−) after thawing, samples were classified as good-freezability (GFE) or poor-freezability (PFE) ejaculates through cluster analyses. The SP activity levels of enzymatic (SOD and PON1) and non-enzymatic antioxidants (CUPRAC, FRAP, and TEAC) were higher (p < 0.05) in GFE than in PFE, whereas SP-OSI was higher (p < 0.05) in PFE than in GFE. In addition, the activity levels of SOD, PON1, GPX, CUPRAC, FRAP, and TEAC were positively (p < 0.05) related to post-thaw sperm motility and plasma membrane integrity and negatively to intracellular ROS levels. The SP-OSI was negatively correlated (p < 0.05) to post-thaw sperm quality parameters and positively to intracellular ROS levels. It can thus be concluded that donkey SP antioxidants are related to sperm cryotolerance and that measurements of antioxidants PON1, SOD, CUPRAC, FRAP, and TEAC, as well as SP-OSI, could be used as markers of sperm cryotolerance. Further research addressing the relationship of these antioxidants and SP-OSI with sperm cryotolerance and their potential use as freezing markers is warranted.